"Risk, uncertainty and profit" - "Knight, Frank H." (New York, 1964)
This essay having gone out of print, the London School of Economics has done its author the signal honour of including it as a number in its series of reprints. In addition, I am accorded the privilege of writing a new preface. Rather than undertake to bring the book down to date in detail, or even to correct mistakes, I am disposed to use this occasion to offer a few comments on the type of economic theory it represents and the lines along which received economic doctrine seems to me to need development and modification, assuming that such endeavour is to be carried on. There are several statements I want placed before any reader of the book under a present date.
Keywords: Economics